ASPECTS OF PERCEPTION AND EVALUATION OF ADAB LITERATURE OF ADYGHE EDUCATORS (BASED ON THE WORK OF A.G. DYMOV) - I. A. KAZHAROVA (Кавказология, 2020)
In this article, based on the material of A. G. Dymov's creative work, some aspects characteristic of the research interpretation of the literature of the adab of the Adyghe enlighteners are revealed. The article considers a number of provisions that were fixed in the fundamental literary works devoted to the progressive trends of confessional education in Kabarda at the turn of the XIX-XX centuries. The degree of correspondence of the concept «adab» to works written by confessionally educated figures of Adyghe culture is established. The article deals with the problem of interpretative limits in literary studies recognized as key for the designated period, and discusses ways to present the works of Adyghe «Arabists» in modern publications: collections and anthologies. The connection between the methods of presentation of the material and the peculiarities of its perception is traced. In order to provide a more accurate and complete scientific understanding of the works under study, the author proves the need to take into account the ideological context of Islamic reformism. In the course of comparing the methods of presentation Of adab by A. G. Dymov in two anthological publications, a rearrangement of semantic accents is revealed, which turns out to be inevitable when reading the «truncated» version of this work. Attention to episodes caused by interpretative limits is important insofar as it involves the need to restore semantic links that could not be represented at the time.